Haematological and certain biochemical parameters in dairy cows of Turkey - Ozdemir, H; Sezer, K; Kilic, S (Indian Veterinary Journal, 2004)
A study was made to evaluate the levels of haematological and certain biochemical parameters in different breeds of dairy cows. The results are presented in this paper.
Keywords: Cattle; Values